Concerning the Identity of the Generations of Islamized Hamshen Armenians - Sahakyan, Lusine (Armenian Folia Anglistika, 2015)
The article considers the consequences of the policy of forced lslamization-Turkification in the Ottoman Empire, particularly, the problem of the present-day Hamshenians’ self-identification. The policy of Islamization conducted by the Ottoman government is characterized as a variety of genocide.